Investigation on energy-efficient retrofitting measures on commercial building external walls in cooling-dominate cities. (2017) - Huang, Yu; Qi, Ronghui; Mi, Lin
Abstract: With the rapid development of modern society, energy consumption is a major concern all over the world. Building energy consumption takes a large proportion in the total energy consumption, and thus attracts much attention. Thermal performance of building envelopes is the determinant factor of building energy consumption. Building envelope retrofitting is an effective way of reducing energy consumption in existing building. For different climates, there may exist different optimal retrofitting schemes. In this paper, two most popular retrofitting methods, namely thermal insulation and high-reflectivity coating on building walls in cooling dominate cities are investigated. Four cities with different climates are selected, and the impacts of internal versus external thermal insulation are investigated. Result indicates that in cooling dominate cities employing both thermal insulation and high reflectivity coating could significantly reduce cooling load through building external wall. Also, performance of retrofitting on different wall surface varies with different orientations. In climates with little diurnal temperature change in the summer season, internal insulation performs better than external insulation in reducing air-conditioning load, which typically operates during part of a day, whereas in climates in which there is a free cooling period during the night, external insulation will perform better.